Ultrastable, high efficiency picosecond green light generation using K3B6O10Br series nonlinear optical crystals. (23rd August 2017) - Hou, Z Y; Xia, M J; Wang, L R; Xu, B; Yan, D X; Meng, L P; Liu, L J; Xu, D G; Zhang, L; Wang, X Y; Li, R K; Chen, C T
Abstract: Two perovskite-structure K3 B6 O10 Br1− x Cl x ( x   =  0 and 0.5) series nonlinear optical crystals were thoroughly investigated for their picosecond 532 nm laser pulses abilities and high power outputs were achieved via second harmonic generation (SHG) technique for the first time. SHG conversion efficiency of 57.3% with a 13.2 mm length K3 B6 O10 Br (KBB) crystal was achieved using a laser source of pulse repetition rate of 10 Hz and pulse width of 25 ps, which is the highest conversion efficiency of ps visible laser based on KBB crystal. And by employing an 80 MHz, 10 ps fundamental laser beam, maximum power outputs of 12 W with K3 B6 O10 Br0.5 Cl0.5 (KBBC) and 11.86 W with KBB crystals were successfully demonstrated. Furthermore, the standard deviation jitters of the average power outputs are less than 0.6% and 1.17% by KBB and KBBC, respectively, showing ultrastable power stabilities favorable for practical applications. In addition, the other optical parameters including acceptance angle and temperature bandwidth were also investigated.